Peranan Wilāyat al-Maẓālim dan Relevansinya dengan Penyelesaian Kasus Pelanggaran Hak Asasi Manusia di Indonesia - Ikhwan Ikhwan (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This article discusses the institution and the aplication of human rights courts in Islamic court system based on data revealed from the books of hadīth, al-sīrah al-nabawīyah, history, Islamic law, and others. From a comparative analysis, it can be concluded that the institution of Wilāyat al-Maẓālim can be seen as human rights court in Islam due to the similarity with the jurisdiction of Indonesian human rights court. If the authority of Indonesian human rights court is limited, that of Wilāyat al-Maẓālim is much wider as to cover the duties and authorities of other state bodies like the Commission of Truth and Reconciliation, State Administration Court, and the Commission of Ombudsman. Various regulations and practices of human rights in Islamic court as played by Wilāyat al-Maẓālim can be used as positive input for building the institution of human rights court.